Afgantsy the Russians in Afghanistan, 1979-89 - Braithwaite, Rodric 1932- (Profile Books, 2011)
Examines the Russian experience in that most recent war in Afghanistan. Largely basing his account on Russian sources and interviews, the author shows the war through the eyes of the Russians themselves - politicians, officers, soldiers, advisers, journalist, women